2021
DOI: 10.1002/ptr.7024
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects and possible mechanisms of Centella asiatica (L.) urban extract against acute and chronic liver injury: Evidence from in vivo and in vitro studies

Abstract: Drug-induced liver injury (DILI) has become a significant health care problem worldwide. Centella asiatica (L.) urban was traditionally used to prevent or treat various diseases, yet whether it works on hepatic injury remains unclear. In this study, multiple experimental models with different damage degrees and types of liver injury have been established to evaluate the hepatoprotective effects of an n-butanol extract of Centella asiatica (CA-BU). Our results revealed that CA-BU improved hepatocyte L02 cells s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Supplementing the rats with CA has a shown to have preventative effect on the breakdown of the antioxidant defense system. Our findings concur with information from related rat research [30,31]. According to this study, CA may have antioxidant capabilities because of its ability to scavenge free radicals and inhibit lipid peroxidation.…”
Section: Discussionsupporting
confidence: 92%
“…Supplementing the rats with CA has a shown to have preventative effect on the breakdown of the antioxidant defense system. Our findings concur with information from related rat research [30,31]. According to this study, CA may have antioxidant capabilities because of its ability to scavenge free radicals and inhibit lipid peroxidation.…”
Section: Discussionsupporting
confidence: 92%
“…Choi et al reported that C. asiatica leaf extract significantly ameliorated increases in ALT and T-bilirubin compared to increases induced by dimethylnitrosamine, which can cause acute and chronic liver injury [29]. The n-butanol extract of C. asiatica protected hepatocyte cell viability against oxidative damage [30]. In a previous study, quercetin, the aglycone form of rutin, exhibited enhanced cytoprotective activity against oxidative stress compared to rutin, the glycoside form [31].…”
Section: Effects Of Triterpenes Against Oxidative Stress In Hepg2 Cellsmentioning
confidence: 99%
“…Antioxidants 2024, 13, x FOR PEER REVIEW 8 of 14 which can cause acute and chronic liver injury [29]. The n-butanol extract of C. asiatica protected hepatocyte cell viability against oxidative damage [30]. In a previous study, quercetin, the aglycone form of rutin, exhibited enhanced cytoprotective activity against oxidative stress compared to rutin, the glycoside form [31].…”
Section: Effects Of Triterpenes On H 2 O 2 -Induced Eahy926 Cellsmentioning
confidence: 99%
“…Some studies used the method of network pharmacology to explore the potential therapeutic targets and biological mechanisms of CA in the treatment of fibrotic disorders, but only one or six compounds were involved [ 12 , 13 , 14 ]. In addition, through the combination of network pharmacological prediction and experimental verification, it was reported in the literature that CA can improve cardiac hypertrophy, hypertrophic scar, and liver injury [ 15 , 16 , 17 ]. The study of network pharmacology regarding CA involved very few components and has not yet been applied to an anti-angiogenesis activity.…”
Section: Introductionmentioning
confidence: 99%